THE MANAGEMENT OF HUMAN RESOURCE DEVELOPMENT IN AR RAIHAN BANDAR LAMPUNG JUNIOR HIGH SCHOOL - Betti Nuraini (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2014)
This case study portrays the human resources development management in Junior HighSchool Ar Raihan Bandar Lampung. It was designed into five stages, i.e. planning, designing(determining), collecting data, analyzing data, and drawing conclusion. The study found that(1) the selection process the teachers’, librarians’ and laboratory personnels’ recruitment wasnil; (2) the recruitment gave priority only to teachers, counselors, and administrative staff;;(3) the employment of librarians and laboratory assistants becomes a second prioritycompared to teachers, counselors, and administrative staff; (5) the school gave an equalrenumeration to the teachers and the education personnel; (6) the focus of human developmentwas on teachers.Keywords: teachers, administration staffs, recruitment, selection, placement, renumeration